EVALUATION OF SUITABILITY FACILITIES FOR ACTIVE FIRE PROTECTION IN PT DOK DAN PERKAPALAN SURABAYA (PERSERO) - Karyati, Anisa; Nawawiwetu, Erwin Dyah (Faculty of Vocational Studies, Universitas Airlangga, 2020)
Background: Every shipyard has a fire hazard that needs to have a sufficient fire protection. PT. Dok dan Perkapalan Surabaya (Persero) has the potential for fire do to hot work and usage of high vultage electricity. Active fire protection facilities at PT. Dok dan Perkapalan Surabaya (Persero) need to be evaluated to ensure that the active fire protection facilities are always in good condition. Purpose: The purpose of this research was to evaluate the application of active protection means in PT. Dok dan Perkapalan Surabaya (Persero) to comply with the rule and standard namely : Permenakertrans No. Per 04/MEN/1980 for fire extinguisher, Permen PU No. 26/PRT/M/2008 and SNI 03-1745-2000 for hydrant. Method: This research was observational descriptive one. The object of this research were : fire extinguisher and hydrant in PT. Dok dan Perkapalan Surabaya (Persero). Data collected by questionnaire,checklist, and observation. Result: The result showed that the active protective means for fire extinguisher in good category with a level of suitability of 92,9% and for hydrant in sufficient condition with a level of suitability of 73,5%. Conclusion:. There were some elements that were not suitable, such as some fire extinguisher covered by items, some fire extinguisher installations exceed 120 cm from the floor surface, some fire extinguisher were defective due to rusting, there were no hydrant use instructions, and no fire hydrant have been examined. PT. Dok dan Perkapalan Surabaya (Persero) is suggested to move items that cover fire extinguisher to be easily seen, the height of the fire extinguisher installation should not exceed 120 cm from Permenakertrans No. Per 04/MEN/1980, replacing inappropriate fire extinguisher, carrying out rountine fire check.